Self-Assessment of mass gathering (Hajj) pharmaceutical care program in Saudi Arabia - Alomi, Yousef Ahmed; Zahran, Razan (Journal of Pharmacy Practice and Community Medicine)
Introduction: Once a year, Muslims of every ethnic group, the Hajj is the fifth and final pillar of Islam. It occurs in the month of Dhul Hijjah which is the twelfth month of the Islamic lunar calendar. It is the journey that every sane adult Muslim must undertake at least once in their lives if they can afford it and are physically able. This study was done to assess pharmaceutical care during mass gathering Hajj period. Method: We performed a questionnaire based on the American model of Center for Diseases Control (CDC) and Institution of Safe Medication Practice (ISMP). It consisted of two part; the first one about necessary demographic information, the second part based on ten selected elements of basic pharmaceutical care. It designed through survey website and distributed through social media. It was at the mid-twelve month of Hijri date September 28, 2015 (15 du alhajia 1436)–January 15, 2016 (5 Rabeea Althani1437). The authors followed the responders with several messages by social media as reminding. The survey analyzed by monkey study. Results: The number of responder at first part sixty responders, with the majority of them pharmacists 52 (86.67%). Of those Males had 48 (80%) and Females 12 (20%). The mean age +/- SD was 65 +/- 20 years. The responders were Represent of Administration of Hajj Services 7 (53.8%), followed by Nurses 6 (46.2%) and clinicians 5 (38.5%), The common diseases in Hajj were Diabetes Mellitus, Hypertension, and Asthma. In the core elements; the high percentages basic elements was reporting information to staff on improving drug therapy during Hajj use and related problem 11(44%). It followed education and research 18 (37.5%) and by Action Support to Optimal Drug Therapy During the month of Hajj Use Policies 35 (36%). The lowest percentages of answered Yes leadership support 5 (19.23%). Conclusion: Mass Gathering Pharmaceutical Care services were limited. Targeting of applying mass gathering clinical pharmacy program, pharmacy infection control, increase clinical pharmacist and distribution pharmacist, mass gathering medication therapy management, and mass pharmacoeconomics program, it improve patients outcome and quality of life and avoid unnecessary health care cost.
Keywords: Mass gathering; Pharmaceutical care; Hajj; Umrah; Assessment; Pharmacist; Saudi Arabia